Pengaruh Pendapatan UMKM Di Kecamatan Siantan, Kabupaten Anambas, Kepulauan Riau - Asyer Ericson Sihombing; Albert Gamot Malau (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
With the large-scale demand for limited job opportunities in Indonesia and the high number of productive workers, MSMEs have become one of the most effective and significant contributors to the national income. MSMEs also succeeded in becoming a main pillar of the Indonesian economy in 2023 by contributing 61% of the GDP equivalent to 9,580 trillion rupiah and employing 97% of the national workforce (approximately 117 million people).This study aims to examine the factors that influence MSME income to help MSME actors in Siantan District improve their income and sales. The analytical method used in this study is the associative-causal method with a quantitative approach. The sample consisted of 30 respondents. Primary data were collected through observation, interviews, and questionnaires. The data analysis technique employed was multiple linear regression analysis.The results indicate that Social Media Marketing, Capital, and Labor have a positive and significant effect on MSME income, whereas Climate has no significant effect on MSME income in Siantan District, Anambas Regency, Riau Islands.